2020
DOI: 10.32734/injar.v3i2.3868
|View full text |Cite
|
Sign up to set email alerts
|

Grain Yield Stability of Rice Genotypes

Abstract: Stability analysis identifies the adaptation of a crop genotype in different environments. The objective of this study was to evaluate promising rice genotypes for yield stability at different mid-hill environments of Nepal. The multilocation trials were conducted in 2017 and 2018 at three locations viz Lumle, Kaski; Pakhribas, Dhankuta; and Kabre, Dolakha. Seven rice genotypes namely NR11115-B-B-31-3, NR11139-B-B-B-13-3, NR10676-B-5-3, NR11011-B-B-B-B-29, NR11105-B-B-27, 08FAN10, and Khumal-4 were evaluated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Significant diversity in agro-morphological traits was reported in rice genotypes by Worede et al. (2014) , Shrestha et al. (2020b) , and Shrestha et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant diversity in agro-morphological traits was reported in rice genotypes by Worede et al. (2014) , Shrestha et al. (2020b) , and Shrestha et al.…”
Section: Resultsmentioning
confidence: 99%
“…There was also a lot of variation in grain production across the twelve coarse rice genotypes (Zahid et al, 2005). Significant diversity in agro-morphological traits was reported in rice genotypes by Worede et al (2014), Shrestha et al (2020b), andShrestha et al (2021).…”
Section: Resultsmentioning
confidence: 99%
“…Grain yield and other characters exhibited stability across the seasons since no significance of year × genotype interaction was detected and the differences among hybrids were apparent. Contrarily, Shrestha et al (2020) found significant interaction between genotypes and year in grain yield.…”
Section: Resultsmentioning
confidence: 87%
“…Government of Nepal (GoN), Nepal Agricultural Research Council (NARC) has been playing a significant role to improve the rice productivity in the country. The current production is not sufficient to meet the demand of growing population and ensure food security in the country (Shrestha et al, 2020a;Shrestha et al, 2020b). However, the results have not been achieved satisfactory.…”
Section: Introductionmentioning
confidence: 97%